2020
DOI: 10.1016/j.ridd.2020.103609
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical development in Williams syndrome: A systematic review

Abstract: Background: The current systematic review is the first to systematically explore and synthesis research to date on mathematical abilities in Williams syndrome (WS), a rare genetic disorder that results in an uneven cognitive profile. As mathematical development is complex and relies on both domain-specific and domain-general abilities, it is currently not clear what mathematical abilities have been examined in WS and also what the current gaps in this research area are. Methods and procedures: A total of 27 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Consistent with previous findings for individuals with ID of mixed etiologies, the few prior studies addressing math achievement for individuals with Williams syndrome (WS)—a rare neurogenetic disorder associated with mild to moderate ID—have reported very low levels of performance (see Van Herwegen and Simms 9 for a systematic review). The purpose of the present study was to describe the full range of math achievement for a relatively large group of children with WS of the same age (9 years) and to identify not only bivariate relations between math achievement and cognitive abilities but also cognitive predictors that accounted for unique variance in math achievement.…”
Section: Introductionsupporting
confidence: 73%
“…Consistent with previous findings for individuals with ID of mixed etiologies, the few prior studies addressing math achievement for individuals with Williams syndrome (WS)—a rare neurogenetic disorder associated with mild to moderate ID—have reported very low levels of performance (see Van Herwegen and Simms 9 for a systematic review). The purpose of the present study was to describe the full range of math achievement for a relatively large group of children with WS of the same age (9 years) and to identify not only bivariate relations between math achievement and cognitive abilities but also cognitive predictors that accounted for unique variance in math achievement.…”
Section: Introductionsupporting
confidence: 73%
“…This finding could be explained by the well-known difficulties of children with DS with counting [36,37]. In addition, considering that, although most individuals with WS have good knowledge of counting names, their understanding of numbers and how they relate to each other is often poor [38], our results suggest that parents of children with WS recognise the difficulties that their children have with mathematics but might underestimate the difficulties that they have specifically with counting. Further studies should investigate if this is the case.…”
Section: Discussionmentioning
confidence: 67%
“…Participants included were from a narrow chronological age range from 10 to 11 years old. This restricted age range was deliberate in order to limit the impact of age as a variable that may contribute to variability in outcomes, as previous studies have shown that large variability in outcomes is often caused by the wide range of ages that are often necessary to include in WS research due to the syndrome's rarity (Van Herwegen et al, 2011). In addition, as these standardized tasks should not be repeatedly used within a time frame of 6 months, two different samples of children were used.…”
Section: Participantsmentioning
confidence: 99%
“…People with WS have mild to moderate IDs with IQs ranging from 42 to 68 (Martens et al, 2008). While there is a similar variability to a neurotypical population (Van Herwegen et al, 2011), individuals with WS have an uneven cognitive profile with areas of relative strength for auditory memory and language, but relatively weak executive functioning for attention, planning, and visuospatial skills (Bellugi et al, 2000;Mervis and Klein−Tasman, 2000;Mervis et al, 2003;Thomas et al, 2011). Again, while there are individual differences to account for, people with WS are often friendly, sociable, and even hyper-sociable (Jones et al, 2000).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation